2020
DOI: 10.5152/tjar.2020.410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Suprainguinal Fascia Iliaca Compartment Block and Patient-Controlled Analgesia for Major Hip Surgeries in Elderly Patients

Abstract: Objective Fascia iliaca compartment block is an alternative analgesic technique for hip surgeries. In the new suprainguinal technique, the ‘bowtie’ sign is detected with an ultrasound probe, and local anaesthetic is injected into the fascial plane with in-plane approach. In this retrospective study, we compared the postoperative analgesic efficacy of suprainguinal fascia iliaca compartment block (S-FICB) and patient-controlled analgesia (PCA) after major hip surgery in elderly patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Chen et al observed significantly lower visual analog scale (VAS) scores at 6 and 12 hours after procedure with 30 mL of 0.2% ropivacaine in SIFI block in comparison to infrainguinal FICB in 50 patients undergoing hip surgeries [1]. Azizoğlu et al demonstrated significantly lower pain scores at rest till 6 hours and pain scores with movement for up to 24 hours post-operatively with 40 mL of 0.25% bupivacaine in USG SIFI in comparison to patient-controlled analgesia with morphine [2]. Though we found no studies comparing different volumes of drug required for SIFI block, the results of studies evaluating the effective volume for the same were corresponding to ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al observed significantly lower visual analog scale (VAS) scores at 6 and 12 hours after procedure with 30 mL of 0.2% ropivacaine in SIFI block in comparison to infrainguinal FICB in 50 patients undergoing hip surgeries [1]. Azizoğlu et al demonstrated significantly lower pain scores at rest till 6 hours and pain scores with movement for up to 24 hours post-operatively with 40 mL of 0.25% bupivacaine in USG SIFI in comparison to patient-controlled analgesia with morphine [2]. Though we found no studies comparing different volumes of drug required for SIFI block, the results of studies evaluating the effective volume for the same were corresponding to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate pain control is an important part of post-operative care for enhanced recovery after surgery as severe pain may lead to an increased stress response and unanticipated hemodynamic changes, which can then trigger major cardiovascular and cerebrovascular complications such as cerebral hemorrhage and myocardial infarction. Thus, early and aggressive application of safe and effective analgesic modalities is essential to improve the outcomes in these patients, especially for older adults with multiple underlying diseases [1,2].…”
Section: Introductionmentioning
confidence: 99%